2020
DOI: 10.1111/jfb.14595
|View full text |Cite
|
Sign up to set email alerts
|

Migration, residency and habitat utilisation by wild and cultured Japanese eels (Anguilla japonica) in a shallow brackish lagoon and inflowing rivers using acoustic telemetry

Abstract: This study monitored post‐release movements of 20 wild Japanese eels (Anguilla japonica) [mean ± S.D. 520.8 ± 92.3 mm total length (TL), 217.9 ± 146.3 g body mass (BM)] in a brackish water lagoon in northeastern Japan using acoustic telemetry to elucidate how wild Japanese eels use different river, estuary and marine environments. In addition, 12 cultured Japanese eels (TL = 578.9 ± 18.0 mm, BM = 344.9 ± 25.5 g) were released to understand the comparative behaviours of wild and cultured eels. Both types of eel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 73 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Variation in migratory life histories among individuals may relate to a complex array of factors, such as condition, energetic status, and sex (Senner et al, 2020), and may have implications for the resilience of eel populations (Moore et al, 2014; Schindler et al, 2010). For instance, extended estuarine residence may allow eels to capitalize on increased food availability (Noda et al, 2021), potentially leading to increased fitness prior to their seaward migration. In contrast, eels remaining in the estuary for an extended period may need to adjust to a constantly changing environment (e.g., salinity) and be subject to greater pressure from predators (e.g., large predatory estuarine fish such as mulloway Argyrosomus japonicus ) or commercial harvesting compared to eels residing in freshwater reaches.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in migratory life histories among individuals may relate to a complex array of factors, such as condition, energetic status, and sex (Senner et al, 2020), and may have implications for the resilience of eel populations (Moore et al, 2014; Schindler et al, 2010). For instance, extended estuarine residence may allow eels to capitalize on increased food availability (Noda et al, 2021), potentially leading to increased fitness prior to their seaward migration. In contrast, eels remaining in the estuary for an extended period may need to adjust to a constantly changing environment (e.g., salinity) and be subject to greater pressure from predators (e.g., large predatory estuarine fish such as mulloway Argyrosomus japonicus ) or commercial harvesting compared to eels residing in freshwater reaches.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in previous studies, the behavioral activity of eels increased at night, with two peaks just after sunset and before sunrise in Japanese eels as well as other eel species [ 23 , 34 , 35 ]. Noda et al [ 24 ] reported the diel movement of yellow Japanese eels; eels move to a river after sunset and return to a brackish lagoon just before sunrise, possibly for foraging purposes [ 38 ]. However, the two peaks of eel climbing are unlikely to be explained only by foraging behavior because eel climbing is likely to be an energy- and time-consuming activity.…”
Section: Discussionmentioning
confidence: 99%
“…We recorded continuously for 24 hours every day from February 13 to May 31, 2021 at a resolution of 1280 × 720 pixels and 30 fps. As anguillid eels are nocturnal [ 23 , 24 ], two infrared lights per camera were lit at night to observe the climbing behavior of eels. To estimate the TL of eels from the video, we painted a white line (AquaCort, HERMETIC, Tokyo, Japan) on top of the weir ( Fig 1C and 1D ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…month, date and season) was also a key driver of movement, with significance reported in 79% of the 14 articles that addressed it. Seaward migration of adults from lentic systems generally peaked during autumn in European eel (Verhelst et al Verhelst, Reubens, et al, 2018), American eel (Winn et al 1975) and Japanese eel (Noda et al 2019(Noda et al , 2021, and late summer in shortfin and New Zealand longfin eel (Jellyman and Unwin 2017;Stuart et al 2019). A seasonal pattern for non-migratory movements is also seen but this may be more variable between location and species.…”
Section: Diel Period and Seasonalitymentioning
confidence: 99%